Social support at work and at home: Dual-buffering effects in the work-family conflict process - Pluut, H.; Ilies, R.; Curseu, P.; Liu, Yukun (2018)
Using experience-sampling methodology, the present study offers a within-individual test of the buffering model of social support in the daily work-family conflict process. Building on the conceptualization of social support as a volatile resource, we examine how daily fluctuations in social support at work and at home influence the process through which work interferes with family life. A total of 112 employees participated in the study and were asked to respond to daily surveys in the work and home domains. Results showed that social support at work and at home—as volatile resources—buffered the daily work-family conflict process within their respective domains. First, a supportive supervisor mitigated the within-individual effect of workload on emotional exhaustion. Second, a supportive spouse protected the strained employee from the effect of emotional exhaustion on work-family conflict, and spousal support also moderated the indirect effect from workload to work-family conflict through emotional exhaustion. The findings suggest that enacting a dual social support system can effectively reduce the adverse effects of excessive job demands on exhaustion and work-family conflict, but buffering effects are highly dependent on the timely availability of social support.